THE CONCEPT OF THE GREEN ECONOMY AND ITS IMPACT ON INDUSTRIAL SECTORS - Fukuda Hiroki (The Conference Hub, 2025)
The article analyzes the theoretical foundations of the green economy concept, its main principles, and its economic, environmental, and technological impacts on industrial sectors. It also examines practical directions for introducing resource-saving technologies, increasing energy efficiency, and reducing the carbon footprint in Uzbek industry. The research results substantiate the increasing importance of environmental factors in industrial development.
Keywords: green economy, sustainable development, industrial sectors, resource efficiency, energy conservation, innovative technologies.